Continuous quality improvement and medical informatics: the convergent synergy. - Werth, G. R. (American Medical Informatics Association, 1992)
Continuous quality improvement (CQI) and medical informatics specialists need to converge their efforts to create synergy for improving health care. Health care CQI needs medical informatics' expertise and technology to build the information systems needed to manage health care organizations according to quality improvement principles. Medical informatics needs CQI's philosophy and methods to build health care information systems that can evolve to meet the changing needs of clinicians and other stakeholders. This paper explores the philosophical basis for convergence of CQI and medical informatics efforts, and then examines a clinical computer workstation development project that is applying a combined approach.